2022
DOI: 10.3389/ijph.2022.1605124
|View full text |Cite|
|
Sign up to set email alerts
|

Longitudinal Association Between Depressive Symptoms and Cognitive Function Among Older Adults: A Latent Growth Curve Modeling Approach

Abstract: Objectives: Although the evidence from numerous longitudinal studies has indicated a remarkable change in cognitive function (CF) and depressive symptoms (DS) over time, the parallel latent growth curve model (LGCM) has seldom been used to simultaneously investigate the relationship between their change trajectories. This study aimed to examine whether a change in DS was associated with CF over time using an LGCM.Methods: Data were collected from the Chinese Longitudinal Healthy Longevity Survey’s 2011, 2014, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(65 reference statements)
0
2
1
Order By: Relevance
“…This decline in cognitive function is relatively steeper than in previous studies (Gao et al, 2022; Zaninotto et al, 2018). For instance, Gao et al (2022) reported that the cognitive function of the MMSE score in older Chinese aged 65 years with severe symptomatic carotid artery stenosis has declined by 0.13 every 3 or 4 years. Also, Zaninotto et al (2018) showed that each cognitive function domain among older people in England has fallen by −0.04 to 0.06 every 2 years.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This decline in cognitive function is relatively steeper than in previous studies (Gao et al, 2022; Zaninotto et al, 2018). For instance, Gao et al (2022) reported that the cognitive function of the MMSE score in older Chinese aged 65 years with severe symptomatic carotid artery stenosis has declined by 0.13 every 3 or 4 years. Also, Zaninotto et al (2018) showed that each cognitive function domain among older people in England has fallen by −0.04 to 0.06 every 2 years.…”
Section: Discussioncontrasting
confidence: 53%
“…Notably, the average score of cognitive function using K-MMSE was 24.39, and we found a cognitive decline of 0.71 every 2 years in our study. This decline in cognitive function is relatively steeper than in previous studies (Gao et al, 2022;Zaninotto et al, 2018). For instance, Gao et al (2022) reported that the cognitive function of the TA B L E 2 Determining the number of latent subgroups according to the cognitive function trajectories (N = 301).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation